Mastectomi pada kucing mastitis - Desty Apritya; Maria Stefani Wae Masa; Murni Hidayah; Zelvy Aprilia; Ivannovich Harawan; Alim Muhsin; Dedi Ardiantama (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
This case was recorded at the Faculty of Veterinary Medicine, University of Wijaya Kusuma Surabaya. Oreo cats were found with a state of weakness, severe dehydration, and a lump in the lower abdomen. The results of the physical examination of Oreo cats were diagnosed as having a mammary carcinoma, with a differential diagnosis of inguinal hernia, and mastitis. To confirm the diagnosis, blood tests and X-ray supporting examinations are carried out. From the results of the examination, the results of the blood check showed normal results, but on the X-Ray examination, there was an intermediate opacity on the part of the bulge and no ring was found that led to the hernia diagnosis. The consistency of the bulge at the time of the xray was slightly changed when compared to when the cat was found, where the consistency of the bulge became slightly flaccid accompanied by a yellowish-white discharge from the oreo cat's nipples. Based on the x-ray results that show the presence of intermediate colored opacity and the discharge of cloudy yellow milk, it can be concluded that the Oreo cat has chronic mastitis. Surgery and removal of the mammary glands (mastectomy) are still the best treatment options. In a mastectomy, the incision is performed in an ellipse, prepared from the surrounding tissue, then the nipple is removed.).